Frontispiece: Characterization at the Level of Individual Crystals: Single‐Crystal MFI Type Zeolite Grains. Issue 10 (16th February 2018) - Gruene, Tim; Li, Teng; van Genderen, Eric; Pinar, Ana B.; van Bokhoven, Jeroen A.
Abstract : Zeolites form an important class of catalysts, for example, zeolite ZSM‐5 finds widespread application in refinery and industry. They build a porous material inwrought with channels and provide a large surface to the catalytic guest reaction. Current research results indicate the presence of a certain type of intergrowth that would interfere with the channel system. However, industrially‐used zeolite grains are too small for many investigations, so that these results are based on samples much larger than what is optimal for the catalytic efficiency. In this issue, T. Gruene, J. A. van Bokhoven et al. onpage 2384 ff. shed new light ‐ or rather: electrons on this question by identifying the single crystal nature of crystals of 100 nm in size.